2010
DOI: 10.1007/978-3-642-15675-5_28
|View full text |Cite
|
Sign up to set email alerts
|

An Approximative Inference Method for Solving ∃ ∀SO Satisfiability Problems

Abstract: The fragment ∃∀SO(ID) of second order logic extended with inductive definitions is expressive, and many interesting problems, such as conformant planning, can be naturally expressed as finite domain satisfiability problems of this logic. Such satisfiability problems are computationally hard (Σ P 2 ). In this paper, we develop an approximate, sound but incomplete method for solving such problems that transforms a ∃∀SO(ID) to a ∃SO(ID) problem. The finite domain satisfiability problem for the latter language is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Recently, Vlaeminck et al [2010] showed how to represent the propagator lim I (V ) by a nested fixpoint definition [Hou 2010]. Methods to evaluate such nested definitions are currently being investigated [Hou et al 2010].…”
Section: Propagators For Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Vlaeminck et al [2010] showed how to represent the propagator lim I (V ) by a nested fixpoint definition [Hou 2010]. Methods to evaluate such nested definitions are currently being investigated [Hou et al 2010].…”
Section: Propagators For Definitionsmentioning
confidence: 99%
“…There exists conformant planning problems where determining whether a conformant plan of length less than a given length l exists is Σ P 2 -hard, even if l is polynomial in the size of the problem. Vlaeminck et al [2010] show how to approximate an MX(∀SO) problem by an MX(FO(ID)) problem, in the sense that solutions of the latter are solutions of the former (but not necessarily vice versa). The representation of FO propagation by a rule set is crucial in the approximation.…”
Section: Approximate Solving Of ∀So Model Expansion Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible to efficiently approximate the set of all models of a theory. We will use here a general approximation method for FO(ID), that efficiently allows us to detect that a formula holds in all models of a theory [17,16]. While we lack space to recall this method in detail, the essence is as follows.…”
Section: The Theory T IImentioning
confidence: 99%
“…An FO(ID) theory T over a vocabulary Σ is syntactically transformed into an inductive definition Approx(T ) over a new vocabulary that contains, for every predicate P/n ∈ Σ, two predicates P ct /n and P cf /n that represent whether P is certainly true (i.e., true in all models of T ) or certainly false (i.e., false in all models of T ). The definition Appox(T ) has the property that if Approx(T ) |= P ct (d), then T |= P (d) (see [16], proposition 5.4) and similar for P cf . In addition, Approx(T ) also defines a number of predicates A ct ϕ and A cf ϕ that tell us whether certain non-atomic formulas ϕ (or their negations, respectively) are entailed by T .…”
Section: The Theory T IImentioning
confidence: 99%